Kontribusi Lembaga Keagamaan dalam Sustainable Development Goals: Analisis Peran Lembaga Pendidikan Muhammadiyah di Indonesia - Tianah, Itaanis; Rahman, Hadiatur; Khairi, Ahmad Imam; Romadhan, Sukron; Qusyairi, Farida Ulfa Lutfiyah (Entita: Jurnal Pendidikan Ilmu Pengetahuan Sosial dan Ilmu-Ilmu Sosial, 2026)
Religious institutions are not limited to being a place to internalize religious values, another vital function is to participate in improving the quality of education for the better with or without assistance from the government. One of the religious institutions that has a contribution to improving quality education is the Muhammadiyah religious institution. This study examines Muhammadiyah religious institutions in Pamekasan. The methods used in this study are qualitative by conducting in-depth observations and interviews. This study interviewed the caregivers of orphanages and administrators of the Pamekasan Muhammadiyah Education Institute and analyzed from a sociological perspective. The contribution of Muhammadiyah Education Institutions can be seen in three aspects; first, striving for quality education for the lower middle class, in order to empower the lower middle class to have equal opportunities to access education. This effort supports SDGs point 4. Second, strengthening soft skills with various programs in orphanages and schools. In addition, it provides free housing and food clothing for students living in orphanages who are on average from the lower middle class, supporting SDGs point 1. Third, providing opportunities for social mobility for the lower class by providing soft skills in the form of book reading skills, memorizing the Qur'an above 10 juices, Arabic and English skills so that they can compete for free S2 and S3 scholarships.